Three-dimensional microcrystalline glass and its manufacturing method
The controlled pre-crystallization and ion exchange process for three-dimensional microcrystalline glass addresses brittleness issues, enabling efficient and cost-effective production with enhanced mechanical properties for 3D applications.
Patent Information
- Application Number
- JP2023557294
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-21
- Filing Date
- 2021-06-18
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-06-18
AI Technical Summary
Existing methods for manufacturing three-dimensional microcrystalline glass face challenges due to its brittleness, which prevents it from being used in 3D hot bending processes, leading to high costs and low yield.
A method involving controlled pre-crystallization, hot bending, and ion exchange treatments to produce three-dimensional microcrystalline glass, using specific raw material compositions and temperature/time controls to achieve desired crystallinity and hardness, followed by ion exchange for enhanced strength.
The method enables low-cost, high-yield production of three-dimensional microcrystalline glass with improved mechanical strength and transparency, suitable for 3D applications, minimizing mold damage and ensuring consistent product quality.
Smart Images

Figure 0007617676000004 
Figure 0007617676000005 
Figure 0007617676000006
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of glass manufacturing, and in particular to three-dimensional microcrystalline glasses and methods for their manufacture. [Background technology]
[0002] Cover glass has undergone the development process from 2D to 2.5D to 3D, so the performance of 3D glass is better than that of traditional 2.5D glass, ceramic cover, and metal back. It is expected that 3D glass will be widely applied to 3C products such as screen covers and back plates of smartphones, smart watches, tablets, dashboards, and other wearable products in the future. 3D glass has the advantages of being light, thin, transparent, clean, anti-fingerprint, anti-glare, weather-resistant, etc., which not only improves the appearance novelty of smart terminal products, but also brings excellent touch feeling. Since smartphones have become the next generation of mobile terminal devices, cover glass has become the standard configuration of most smartphones. In fact, the design concept and processing mode of cover glass are mainly based on the experience of the deep processing industry of watch glass lenses. As can be seen from the design and application of watch glass lenses, 3D curved glass has a better appearance expression mode and better protection effect than 2D flat glass. Among them, the double curvature 3D curved glass is particularly preferred, and is obviously superior to the 2D flat glass in terms of drop prevention, scratch prevention, and hydrostatic pressure test. In recent years, OLED (organic light-emitting diode) curved screens have increasingly become the trend of smartphone application, and thanks to this, the 3D glass cover that adopts the arc design and fits the curved screen also stands out. In the 5G era, the application of wireless communication technologies such as NFC (near field communication technology), WiFi (wireless fidelity), and LIFI (visible light wireless communication) is becoming more widespread, and the metal body will block or interfere with the signal to a certain extent. Smartphones can solve this problem well by using 3D glass display screens and 3D glass back covers. In addition, because the 3D glass adopts an arc design, it has the advantages of smooth touch, light and thin texture, transparent and clean, and anti-glare.
[0003] Microcrystalline glass, also called microcrystalline boulders or ceramic glass, is composed of a crystal phase and a glass phase, and therefore has the dual properties of glass and ceramic. The crystal phase in microcrystalline glass ensures the inherent strengthening mechanism of classical microcrystalline glass, while the remaining glass phase of microcrystalline glass can also be chemically strengthened, thus giving microcrystalline glass high strength, high hardness and high scratch resistance. In addition, microcrystalline glass has a natural and soft texture, and can obtain a variety of colors through composition and process control. Therefore, the trend of microcrystalline glass covers entering the market is also remarkable.
[0004] At present, microcrystalline glass has a significant content of crystalline structure, which significantly reduces the softening effect at high temperatures compared with glass, and has some of the brittleness of ceramics, so it cannot be subjected to the 3D hot bending process. The production of 3D curved microcrystalline glass by buffing process is complicated, has low yield, and keeps molding cost high. This problem greatly hinders the application of microcrystalline glass in the field of 3D cover materials. Summary of the Invention [Problem to be solved by the invention]
[0005] SUMMARY OF THE PRESENT DISCLOSURE In order to overcome the shortcomings of the prior art, the present invention provides a low-cost and highly efficient method for producing three-dimensional microcrystalline glass and a product produced using the same. [Means for solving the problem]
[0006] The specific technical solution of the present invention is a method for producing three-dimensional microcrystalline glass, Step 1 is to prepare raw materials, and weigh out and mix uniformly the following components by weight: SiO2: 63-75%, Al2O3: 4-10%, TiO2: 0-4%, CaO: 0-1%, MgO: 0-1%, Li2O: 8-11%, Na2O: 0.1-3%, K2O: 0.1-1%, P2O5: 1-5%, ZrO2: 1-6%, BaO: 0-1%, Sb2O3: 0-2%, Y2O3: 0-0.5%; Step 2: The raw material obtained in step 1 is transferred to a platinum crucible, the platinum crucible is placed in a high-temperature furnace, and the temperature is gradually increased to 1500°C-1600°C. The temperature is kept for 2-24 hours, and the raw material is melted by bubbling and homogenization treatment (the purpose of bubbling is to remove small bubbles in the glass and remove bubbles in the glass liquid). The molten liquid is then poured into a preheated mold to be molded, and then annealed at 300-550°C for 2-12 hours to obtain a precursor glass block. Step 3, obtaining a precursor glass sheet after CNC machining the precursor glass block obtained in step 2; The precursor glass sheet obtained in step 3 is subjected to a pre-crystallization treatment, specifically, first, it is heated at 540-590°C for 0.5-5 hours (h), and then it is heated at 600-800°C for 0.5-2 hours to control the crystallinity of the pre-crystallized glass to 10-46%, and the formed crystals are lithium disilicate, lithium silicate and / or petalite, specifically, lithium disilicate 5-20wt%, lithium silicate 5-20wt%, petalite 0-6wt%. The hardness of the pre-crystallized glass is 5000-6500Kg / cm 2 Step 4 is to control the hardness of the pre-crystallized glass within this range, which is necessary to apply a certain pressure so that the final product has a good forming effect in the subsequent hot bending process. If the hardness of the pre-crystallized glass is not controlled, it is easy to damage the forming die. Step 5 is to control the hardness of the pre-crystallized glass within this range, which minimizes the damage to the hot bending die. Step 5 includes hot bending, and the pre-crystallized glass sheet obtained in step 4 is first subjected to a pre-heating treatment, then a forming treatment, and finally a cooling treatment, and after cooling to room temperature, a three-dimensional microcrystalline glass can be produced.
[0007] The preheating treatment in step 5 is divided into six process sections, the temperature of the first process section is 350-500°C, the temperature of the second process section is 440-580°C, the temperature of the third process section is 530-660°C, the temperature of the fourth process section is 590-670°C, the temperature of the fifth process section is 590-680°C, and the temperature of the sixth process section is 620-650°C, and the time of each process section is 90-150s.
[0008] The molding step in step 5 is divided into three process sections, among which the molding step is divided into three process sections, the temperature of the first process section is 690-780°C, and the pressure applied by the mold is 3-6Kg / cm 2 The temperature of the second process is 740-800°C, and the pressure applied by the mold is 5-7Kg / cm 2 The temperature of the third process is 730-810℃, and the pressure applied by the mold is 8-9Kg / cm 2 The time of each process section is 90-150s. In this process, pressure is applied to the glass through the mold, and the movement and expansion of the glass in the mold is hindered through the real object, thereby realizing the reduction of the deformation of the glass during the crystallization process, and the pressure is applied to rapidly heat the glass to the crystallization temperature. Also, pressure is applied to the glass through the mold to allow crystallization in a short duration. The pressurization is completed by one or more process sections, the residence time of each process section is 90-150s, and the mold pressure in the hot bending forming process is 3-9Kg / cm 2 If the pressure is too low, the hot bending effect is insufficient. If the pressure is too high, it will cause graphite marks on the glass surface after hot pressing. The hot bending forming temperature is 30℃-60℃ above the glass expansion softening point temperature. The hot bending is completed by one or more process sections, the residence time of each process section is 90-150s, and the hot bending temperature is preferably controlled at 720℃-820℃. When crystallizing at a high temperature, a slight auxiliary pressure is applied, which is helpful in preventing deformation phenomenon during glass crystallization.
[0009] The cooling stage in step 5 is divided into four process sections, the temperature of the first process section is 720-800°C, the temperature of the second process section is 670-730°C, the temperature of the third process section is 550-630°C, and the temperature of the fourth process section is 550°C, and the time of each process section is 90-150s. Finally, the glass is cooled slowly at a rate of 0.1°C / s-8°C / s back to room temperature, and the glass is exposed to a room temperature environment, thereby cooling the glass from the crystallization temperature to room temperature.
[0010] The method further includes step 6 of subjecting the three-dimensional microcrystalline glass obtained in step 5 to an ion exchange strengthening treatment, in which the three-dimensional microcrystalline glass is first immersed in a salt bath of molten NaNO3 at a temperature of 420°C to 460°C for 3 to 12 hours to perform ion exchange, and then the three-dimensional microcrystalline glass is immersed in a salt bath of molten KNO3 at a temperature of 400°C to 460°C for about 2 to 10 hours to perform ion exchange.
[0011] It is a three-dimensional microcrystalline glass, the raw materials for its production are expressed in mass fraction based on oxides, and contain SiO2: 63-75%, Al2O3: 4-10%, TiO2: 0-4%, CaO: 0-1%, MgO: 0-1%, Li2O: 8-11%, Na2O: 0.1-3%, K2O: 0.1-1%, P2O5: 1-5%, ZrO2: 1-6%, BaO: 0-1%, Sb2O3: 0-2%, and Y2O3: 0-0.5%. The glass crystal content of the finished product is lithium disilicate: 30-45%, petalite: 30-45%, and the transparency of the three-dimensional microcrystalline glass can be guaranteed. It should be understood that the chemical properties of petalite and lithium disilicate are close to those of the remaining glass body, the refractive index difference is small, and the components change continuously; therefore, the higher the proportion of petalite and lithium disilicate in the crystal phase, the higher the transmittance of the three-dimensional microcrystalline glass in the visible light region.
[0012] The hardness of the three-dimensional microcrystalline glass is 8500Kg / cm 2 However, if the Vickers hardness is too high, it may be difficult to process, so the Vickers hardness of the glass of this three-dimensional shape is 11,000 kg / cm 2It is preferable that the resistance is less than 10,500 kg / cm 2 More preferably, it is 10,000 kg / cm or less. 2 It is even more preferable that:
[0013] The average grain size of the crystal phase in the three-dimensional microcrystalline glass is less than 100 nm, and preferably, the average grain size of the crystal phase in the three-dimensional microcrystalline glass is 20 nm to 70 nm.
[0014] On the one hand, the present invention adjusts the sequence of hot bending and microcrystallization, so that the flat glass is first subjected to pre-crystallization nucleation treatment, so that it has a crystallinity of 20%-40% and a crystal grain size of 2-15nm, and then hot bending is performed to obtain three-dimensional microcrystalline glass. The hot bending step is set after pre-crystallization, that is, the pre-crystallized glass product is placed in the hot bending mold to perform hot bending. Before the hot bending step, the microcrystalline glass forms crystal nuclei, but the crystal phase does not grow, so the crystallinity is low and the hardness is low, which is favorable for hot bending.
[0015] On the other hand, the present invention controls the temperature and time in the pre-crystallization process to produce a certain crystal type transformation. With the composition of the raw material of the present invention, combined with the temperature and time in the pre-crystallization process, lithium disilicate and lithium silicate are more likely to form and nucleate, the nucleation glass with lithium disilicate and lithium silicate has good bending performance, and the content of crystal in the glass makes the nucleation glass ideal for 3D hot bending. After keeping at a certain temperature for a certain time, the structural relaxation of the glass undergoes significant changes, and the lithium silicate crystal gradually transforms into lithium disilicate, and the proportion of lithium silicate and lithium disilicate gradually decreases, specifically Li2SiO3+SiO2=Li2Si2O5, where SiO2 is from the glass substrate. When the main crystal phase of glass is transformed into Li2Si2O5, the breaking strength of glass is greatly improved, and its flexural strength is also improved. With the continuation of hot bending, the petalite crystals in the product gradually increase. There are two reasons for the precipitation of petalite: first, Li2O, Al2O3 and SiO2 in the glass matrix further form petalite crystals under certain conditions; second, lithium disilicate and / or lithium silicate in the nucleation glass react with SiO2 in the glass matrix to form petalite crystals, i.e. Li2Si2O5+6SiO2+Al2O3=2LiAlSi4O 10 and / or Li2SiO3+7SiO2+Al2O3=2LiAlSi4O 10 The lithium silicate is totally dissolved or only small amounts remain in the final product, and the predominant crystalline phases are petalite and lithium disilicate.
[0016] In addition, the three-dimensional microcrystalline glass produced by the technical solution of the present invention can further undergo ion exchange, thereby obtaining a strengthened glass with higher strength. Specifically, the three-dimensional microcrystalline glass is placed in a NaNO3 or KNO3 salt bath to carry out ion exchange, and in the ion exchange process, one-dimensional ion exchange of potassium-sodium or sodium-lithium can be carried out, and two-dimensional ion exchange of potassium-sodium and sodium-lithium mixture can also be carried out, in which the large-diameter alkali metal ions are potassium and sodium ions, and the small-diameter alkali metal ions are sodium and lithium ions. The large-diameter alkali metal ions in the salt bath replace the small-diameter alkali metal ions in the glass, and a complex compressive stress is generated in the three-dimensional microcrystalline glass due to the "crowding effect". The Vickers hardness of the strengthened product is 9000-11000Kg / cm 2 The glass product with a thickness of 8mm has a transmittance of more than 85% in the wavelength range of 400-800nm. This 3D microcrystalline glass has a high Vickers hardness and is not easily damaged.
[0017] This product has different ranges of hardness at different stages by controlling the type and degree of crystallinity of the crystals at different stages in the manufacturing process, so that the final product has ideal mechanical strength and the damage caused to the mold during the production process can be controlled to a minimum. For example, the main crystal phase of the crystal precipitated in the pre-crystallization stage by adjusting the ingredients, time and temperature is lithium disilicate and lithium silicate, and the crystallinity of the crystal is 20-40%, and the hardness of lithium disilicate and lithium silicate is lower than that of petalite precipitated in the final product, so that the die does not accelerate the wear rate due to the pre-crystallized glass having too high hardness during the hot bending process, and the main crystal phase of the crystal precipitated in the glass after hot bending is petalite and lithium disilicate, and the crystallinity is within the range of 60-90%, so that the final product has ideal mechanical properties. By controlling the crystallinity of pre-crystallization within the range of 20-40%, it can be ensured that the crystallinity of the pre-crystallized glass is not too high during the hot bending process, which causes difficult forming, and that the crystallinity of the final product does not reach the ideal range due to the crystallinity of the pre-crystallized glass being too low, which causes the product to have insufficient mechanical properties. Effect of the Invention
[0018] The technical solution of the present invention avoids the problem that after the flat glass has been completely and thoroughly microcrystallized, it has some ceramic brittleness and cannot be subjected to 3D hot bending process, and also avoids the problem that in the method of bending and forming amorphous glass and then crystallizing it, when heating is performed after forming, it is not only easy to deform, but also the dimensional change occurs when the amorphous glass is crystallized, making it difficult to obtain the desired shape. Compared with the prior art, the technical solution of the present invention first performs glass microcrystallization treatment on a flat surface to obtain flat microcrystalline glass, and then adopts a buffing process to manufacture the flat microcrystalline glass into a 3D curved microcrystalline glass, and the manufacturing process provided by the present invention has the advantages of high yield and low process cost. [Brief description of the drawings]
[0019] [Figure 1] FIG. 2 is a schematic diagram of the crystal formation principle corresponding to different process sections. [Diagram 2] 1 is an XRD spectrum analysis of the pre-ceramic glass produced in Example 1. [Diagram 3] 1 is an XRD spectrum analysis of the glass produced in Example 1 after hot bending. [Figure 4] 1 shows the transmittance spectrum in the 280-800 nm range of the three-dimensional microcrystalline glass produced in Example 1. [Diagram 5] FIG. 2 is a model diagram of a hot-bent product of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] As a result of intensive research and testing, the inventors of the present invention have determined that the content and content ratio of specific components constituting the microcrystalline glass product are set to specific values, and specific crystal phases are precipitated to obtain the microcrystalline glass or glass product of the present invention at low cost. The composition range of each component of the microcrystalline glass of the present invention is described below. In this specification, the content of each component is expressed as a weight percentage relative to the total amount of glass material in oxide-equivalent composition unless otherwise specified. Here, the "oxide-equivalent composition" refers to the case where the oxides, composite salts, etc. used as raw materials for the composition components of the microcrystalline glass of the present invention are all decomposed and converted into oxides during melting, and the total amount of substance of the oxides is 100%.
[0021] The compounded materials are weighed according to the glass 1 oxide mass percentage in Table 1 and mixed to obtain a uniform material, then the compounded materials are transferred to a platinum crucible of about 800 ml, the platinum crucible is placed in a high-temperature furnace, gradually heated to 1540 ° C, kept at the temperature for 6 hours, and homogenized by removing bubbles by bubbling, etc. Next, after 10 hours of clarification, the molten liquid is poured into a preheated mold to be molded, then it is transferred to a box-type annealing furnace and annealed at 500 ° C for about 4 hours, and then naturally cooled to room temperature to produce a precursor glass block. The obtained precursor glass block is cut into 0.8 mm glass sheets with a single-wire diamond line saw. The obtained glass sheets are CNC machined to finally obtain the required precursor glass.
[0022] The resulting precursor glass required for the final stage is first subjected to a pre-crystallization treatment by keeping it at 550°C for 3 hours (h) and then at 660°C for 2 hours.
[0023] The pre-crystallized glass is then hot-bent, and the pre-heating step is first performed during the hot-bending process. The pre-heating step is divided into six process sections, the temperature of the first process section is 380°C, the temperature of the second process section is 440°C, the temperature of the third process section is 530°C, the temperature of the fourth process section is 590°C, the temperature of the fifth process section is 610°C, and the temperature of the sixth process section is 630°C, and the residence time of each process section is 120s. Next, the forming step is performed. In this embodiment, the forming step is divided into three process sections, the temperature of the first process section is 700°C, and the pressure applied by the mold is 4Kg / cm. 2 The temperature of the second process is 750°C, and the pressure applied by the mold is 6Kg / cm 2 The temperature of the third process is 740°C, and the pressure applied by the mold is 8Kg / cm 2The temperature of the first step is 730° C., the temperature of the second step is 680° C., the temperature of the third step is 640° C., the temperature of the fourth step is 590° C., and the temperature of the fifth step is 550° C., and the residence time of each step is 120 s.
[0024] Then, the molded glass product is immersed in a molten salt of NaNO3 at 430°C for 7 hours, and then kept in a molten salt of KNO3 at 450°C for 3 hours to carry out ion exchange to obtain a final product, the main crystal phase of which is petalite and lithium disilicate, of which the transmittance of the product is 90%, the hardness after pre-crystallization is 560MPa, the hot bending glass hardness is 870MPa, the glass hardness after tempering is 1020MPa, the glass CS value after tempering is 400MPa, and the DOC is 10μm.
[0025] The experimental data for Examples 1-8 are shown in Tables 1 and 2.
[0026] [Table 1]
[0027] [Table 2] JPEG0007617676000003.jpg170167
[0028] It should be noted that the above embodiments are described in this specification, but they do not limit the scope of protection of the claims of the present invention. Therefore, based on the novel concept of the present invention, any changes and modifications made to the above embodiments of this specification, or equivalent structure or equivalent flow conversion made by utilizing the contents of the specification and drawings of the present invention, directly or indirectly apply the above technical solutions to other related technical fields, all of which are included in the patent protection scope of the present invention.
Claims
1. A three-dimensional microcrystalline glass, the manufacturing raw materials of which are expressed in mass fraction based on oxides, and the mass fractions are as follows: SiO2: 63-75%, Al2O3: 4-10%, Li2O: 8-11%, Na2O: 0.1-3%, K2O: 0.1-1%, P2O5: 1-5%, ZrO2: 1-6%, TiO2: 0-4%, CaO: 0-1%, MgO: 0-1%, BaO: 0-1%, Sb2O3: 0-2%, Y2O3: 0-2%, and SiO2: 63-75%. A method for producing three-dimensional microcrystalline glass, comprising: 0-0.5% lithium disilicate; the main crystal phase of the finished glass crystal is lithium disilicate and petalite; and the three-dimensional microcrystalline glass having a thickness of 0.8 mm has a transmittance of 90% or more at wavelengths of 400 nm to 800 nm, The raw materials were prepared and calculated by weight percentage as follows: SiO 2 :63-75%, Al 2 O 3 :4-10%, TiO 2 :0-4%, CaO:0-1%, MgO:0-1%, Li 2 O: 8-11%, Na 2 O: 0.1-3%, K 2 O: 0.1-1%, P 2 O 5 : 1-5%, ZrO 2 :1-6%, BaO:0-1%, Sb 2 O 3 : 0-2%, Y 2 O 3 Step 1: Weigh out 0-0.5% and mix uniformly; Step 2: the raw material obtained in step 1 is transferred to a platinum crucible, the platinum crucible is placed in a high-temperature furnace, the temperature is gradually increased to 1500°C-1600°C, and the temperature is maintained for 2-24 hours. The melt is then melted by bubbling and homogenization treatment, and the melt is then poured into a preheated mold to be molded, followed by annealing at 300-550°C for 2-12 hours to obtain a precursor glass block; Step 3: obtaining a precursor glass sheet after CNC machining the precursor glass block obtained in step 2; Step 4 is a step of pre-crystallizing the precursor glass sheet obtained in step 3, which is first kept at 540-590°C for 0.5-5 hours, and then kept at 600-800°C for 0.5-2 hours to control the pre-crystallized crystallinity of the glass to 10-46%; Step 5: subjecting the pre-crystallized glass sheet obtained in step 4 to a hot bending process, the hot bending process first includes a pre-heating stage, then a forming stage, a cooling stage, and finally cooling to room temperature to produce a three-dimensional microcrystalline glass; A method for producing three-dimensional microcrystalline glass, comprising:
2. 2. The method for producing three-dimensional microcrystalline glass according to claim 1, wherein the crystals formed in the preliminary crystallization treatment in step 4 are lithium disilicate, lithium silicate and / or petalite.
3. The method for producing three-dimensional microcrystalline glass according to claim 1, characterized in that the pre-heating step of step 5 is divided into six process sections, the temperature of the first process section is 350-500°C, the temperature of the second process section is 440-580°C, the temperature of the third process section is 530-660°C, the temperature of the fourth process section is 590-670°C, the temperature of the fifth process section is 590-680°C, and the temperature of the sixth process section is 620-650°C, and the time of each process section is 90-150s.
4. The molding step of step 5 is divided into three process sections, of which the temperature of the first process section is 690-780°C and the pressure applied by the mold is 3-6Kg / cm 2 The temperature of the second process is 740-800°C, and the pressure applied by the mold is 5-7Kg / cm 2 The temperature of the third process section is 730-810°C, and the pressure applied by the mold is 8-9 kg / cm 2 The method for producing three-dimensional microcrystalline glass according to claim 1, characterized in that the time for each process section is 90-150 s.
5. The method for producing three-dimensional microcrystalline glass as claimed in claim 1, characterized in that the cooling stage of step 5 is divided into four process sections, the temperature of the first process section is 720-800°C, the temperature of the second process section is 670-730°C, the temperature of the third process section is 550-630°C, and the temperature of the fourth process section is 550°C, and the time of each process section is 90-150s.
6. Step 6 is to subject the three-dimensional microcrystalline glass obtained in step 5 to an ion exchange strengthening treatment, and the three-dimensional microcrystalline glass is first subjected to ion exchange strengthening treatment with molten NaNO at a temperature of 420° C. to 460° C. 3 The ion exchange is carried out by immersing the three-dimensional microcrystalline glass in a salt bath at 400°C to 460°C. 3 2. The method for producing three-dimensional microcrystalline glass according to claim 1, further comprising step 6: immersing the glass in a salt bath of about 1000 g for about 2 to 10 hours to carry out ion exchange.
Citation Information
Patent Citations
Crystallized glass
JP2009114005A
Glass-ceramics and substrates thereof
JP2021509658A
Coated microcrystalline glass with improved water-repellent and oil-repellent property, preparation method and application therefor
JP2022117461A
Crystallized glass, crystallized glass product and manufacturing method
JP2023506666A
Glass-ceremic article and glass-seramic for electronic device cover plate
US20200131080A1